Synthesis and characterization of nanostructured photoanodes for dye sensitized solar cells. Issue 16 (November 2019) - Khan, M.I.; Rehman, M.A.; Saleem, Muhammad; Baig, M.R.; Rehman, S.; Farooq, W.A.; Atif, M.; Hanif, Atif
Abstract: To improve efficiency of charge collection of dye sensitized solar cells (DSSCs), nano rods of TiO2, Zn doped TiO2, Zn & Cu co-doped TiO2 have been prepared by using sol-gel technique on FTO glass substrates. Polyethyleneimine (PEI) was used in the seed sole as a surfactant to prepare nanorods of TiO2 . These nanorods are used for DSSC as photoanodes. SEM micrographs show the increasing behavior in diameter and length of nanorods by increasing the doping concentration of Zn and Cu. UV–Vis absorption results showed that in UV region at the wavelength 380 nm, formation of anatase TiO2 is confirmed by one strong absorption peak of all samples. The dye adsorption peak is observed at 530 nm. Due to increase in the length of nanorods, an increasing behavior in the intensity of the UV–vis absorption peak was observed. Solar simulator results of the cell formed by co doping of 0.5% Zn and 2% Cu in TiO2 shows large current density (JSC ) 6.67 mA-cm −2, open circuit voltage (VOC ) 0.7 V and fill factor (FF) 0.65 as compared to other electrodes, resulting high efficiency 3%.